PENGARUH MINAT BELAJAR TERHADAP PRESTASI BELAJAR SISWA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Fida Nur Kholidah; Noor Amirudin (Fakultas Agama Islam Universitas Muhammadiyah Luwuk, 2023)
Islamic religious education is a subject that contains material about morals and morals. Therefore knowing learning achievement. in Islamic religious. education subjects is important because it is an indicator that a student has good morals and character. This study. aims to determine. the effect of interest in learning on student. achievement in. Islamic religious education. subjects. The data used is primary data in the form of a questionnaire and secondary. data in the form of student report cards in the odd semester of the 2022/2023 school year. This study. was analyzed using a simple. regression analysis. technique with the help of statistical tools e-views version 12. The findings of this study indicate that interest in learning has a positive. and significant. effect on student. achievement in Islamic. religious education. subjects. In addition, this study. also found. that learning achievement was influenced by an interest in learning by 85.5%. Therefore, to improve. student learning achievement. in Islamic religious. education, a teacher is expected to be able to increase student interest in learning by using various teaching tools such as visual aids, videos, and so on.